2020
DOI: 10.1155/2020/7850179
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Soluble Urokinase Plasminogen Activator Receptor Is Related to Disease Activity of Patients with ANCA-Associated Vasculitis

Abstract: Objective. The soluble urokinase plasminogen activator receptor (suPAR) is associated with kidney diseases and is used as a prognostic factor of renal function progression. The aim of this study was to explore whether circulating suPAR was associated with antineutrophil cytoplasmic autoantibody- (ANCA-) associated vasculitis (AAV) disease activity. Methods. We evaluated 90 AAV patients with follow-up data and 35 normal controls; their plasma suPAR and C-reactive protein (CRP) levels were measured by ELISA. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…While, there was no correlation of sUPAR with age or sex of the patients. This was in line with Huang et al, who did not find any correlation of sUPAR with age or gender of patients with HCV with hepatic fibrosis [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While, there was no correlation of sUPAR with age or sex of the patients. This was in line with Huang et al, who did not find any correlation of sUPAR with age or gender of patients with HCV with hepatic fibrosis [10].…”
Section: Discussionsupporting
confidence: 91%
“…It has been found that sUPAR has an important role in inflammation, proteolysis and tissue remodeling. Accordingly, sUPAR level is strongly elevated in acute liver failure and advanced chronic liver diseases, especially in decompensated cirrhosis, indicating that hepatic inflammation in principle is linked to hepatic UPAR expression and sUPAR release [10].…”
Section: Introductionmentioning
confidence: 99%
“…SuPAR levels in 90 AAV patients were assessed, and it was found that they were significantly higher than in HC patients. Additionally, suPAR was found to be significantly higher in AAV patients who were in active stages of the disease compared to those who were in partial remission, indicating a link between disease activity and a poor prognosis [45]. Similar findings were found in another study by Rowaiye et al where 60 patients with renal involvement and AAV have been followed up for a median period of 12 months with higher levels of suPAR in patients with relapse compared with patients with inactive AAV.…”
Section: Anca-associated Vasculitis (Aav)supporting
confidence: 84%
“…In a number of studies, it has been suggested that the suPAR level reflects the activation state of the immune system [ 42 , 43 , 44 , 45 ]. There are a few studies suggesting that the suPAR plasma level can be considered a biomarker in AAV as well [ 78 ]. The results of our study confirm that an elevated level of the suPAR is associated with the AAV disease, and that its increased level is related to AAV-related deterioration of the kidney function.…”
Section: Discussionmentioning
confidence: 99%